‘Verdreeven om de getuygenisse der waarheid’. Over bevindelijke vroomheid in de Kaapkolonie - Schutte, G (Nederduitse Gereformeerde Teologiese Tydskrif, 2010)
On May 11, 1751 Governor Rijk Tulbagh ordered the Reverend Herman Hayko van der Veen (a former minister in East Frisia, now recruited by the VOC for the church in the East) to continue his journey to Batavia immediately. An officer of the garrison escorted him to Table Bay. And some forty Capetonians. At the beach he kneeled for a prayer. I am being chased from the Cape because I bear witness God’s truth! Since his arrival at the Cape, on the 21th of January, Van der Veen had created many conflicts, with the local clergy, the consistory, and the government. But he had also edifyed scores of godfearing people in a conventicle: Van der Veen was a pietist, preaching conversion and revival. His story and some other more give substance to a forgotten element of 18th century Cape religious life: Calvinist experiental pietism.